Rancang Bangun Sistem Monitoring Fasa dan Daya berbasis Internet of Things (IoT) menggunakan Smartphone - suprihartini, yayuk; Indah Sucita, Laras (Politeknik Penerbangan Makassar, 2021)
Distribution system is one of the systems in electrical power that has an important role because it is directly connected with users. Usually there are often unbalanced loads and phase failure on three phase distribution system. Measuring tools here are needed in online monitoring to find out the real time value of a distribution system. Phase and power monitoring tool will be designed in a three-phase distribution system that use the internet so that it can be accessed remotely and uses Arduino Mega, Wemos D1 Mini device with PZEM-004T sensor. So that the display of monitoring results can be accessed via smartphone device using the Blynk application